Вплив доменної структури сегнетоелектричної пiдкладки на провiднiсть графену - Kurchak, A. I. (Publishing house "Academperiodika", 2019)
The review is devoted to the recent theoretical studies of the impact of the domain structure of a ferroelectric substrate on the graphene conductance. An analytical description of the hysteresis memory effect in a field effect transistor based on graphene-on-ferroelectric, taking into account absorbed dipole layers on the free surface of graphene and localized states on its interfaces is considered. The aspects of the recently developed theory of p–n junctions conductivity in a graphene channel on a ferroelectric substrate, which are created by a 180-degree ferroelectric domain structure, are analyzed, and the cases of different current regimes from ballistic to diffusion one are considered. The influence of size effects in such systems and the possibility of using the results for improving the characteristics of field effect transistors with a graphene channel, nonvolatile ferroelectric memory cells with random access, sensors, as well as for the miniaturization of various devices of functional nanoelectronics are discussed.